A Research on the Satisfaction of Islamic Banking Customer Services in Riau Province During the Covid-19 Pandemic - Boy Syamsul Bakhri (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2021)
This research is motivated by curiosity about Islamic banking services in Riau Province during the Covid-19 pandemic. But before that, it is also important to examine customer knowledge on products and service facilities in Islamic banking, reasons customers choose Islamic banks, and reasons customers use both types of banks (Islamic banking and conventional banking). This research is a field research with survey technique. The population is Islamic banks customers in Pekanbaru and the samples in this study refer to the calculation of Hair et al with total assets of Islamic banks in 2020 as a consideration in determining proportional allocation. Sources of data in this research are primary and secondary data. While the data collection techniques using questionnaires and documentation. The data analysis technique uses descriptive statistics with a frequency distribution. The results of the research found that there are still many Islamic bank customers who do not know about specific Islamic bank products such musyarakah products, mudharabah products, ijarah products,and rahn services. The results also found that religious reasons are the main factor for customers in choosing of Islamic banks. The factor of ease of access to more branches is the main reason customers use both types of banks. Finally, the results of the research found that the most Islamic bank customers are satisfied with various aspects of the services provided by Islamic banks, while the five service aspects whith the highest level of customer satisfaction are Islamic bank staff friendliness, Islamic bank name and image, Islamic bank employee skills, confidentially Islamic bank customer data, as well as various kinds of facilities offered by Islamic banks. The results of this research are ini line with studies that have been conducted in Jordan and Kuwait, where the highest level of satisfaction is found in the name and image aspects of Islamic banks even though there are differences in respondent demographics and the condition of the Covid-19 pandemic.